Pengaruh Talent Management terhadap Turnover Intention melalui Kepuasan Kerja Karyawan pada Hotel Grand Zuri Pekanbaru - Fadhila Rafliani; Kasmiruddin Kasmiruddin (Departement of Mathematics Education, 2023)
This study at the Grand Zuri Hotel Pekanbaru seeks to ascertain the impact of talent management on employee job satisfaction and turnover intention.. The independent variable is talent management (X) and the intermediary or mediating variable is job satisfaction (Z). while the dependent variable is turnover intention (Y). A questionnaire with Likert scale measurements is used in this study. Using the software SmartPls 4.0, perform a linear regression analysis. 90 Grand Zuri Hotel Pekanbaru staff members made up the study's population. Using the total census/sampling method as the sample technique. From the results of the tests conducted, it shows that talent management has a negative and significant effect on talent management, talent management has a positive and significant effect on job satifsfaction, job satisfaction has a negative and significant effect on turnover intention and talent management has a negative and significant effect on turnover intention through job satisfaction.